Factors to develop an index of vulnerability to contamination in urbanized coastal karst aquifers - Uhu-Yam, Wilbert David; Frausto-Martínez, Oscar; Rodríguez- Castillo, José Francisco; Colín-Olivares, Orlando (Ecosistemas y Recursos Agropecuarios, 2022)
The aim of this work is to propose and analyse factors for the construction of an index of vulnerability to contamination of urbanised coastal karst aquifers. Due to the high anthropic modifications of the territories, the city of Playa del Carmen, Quintana Roo, was taken as the study area. Four factors were addressed: relief, climate, sea level rise and land use. For relief, depressions were identified using LiDAR data from INEGI. The climate factor was worked with meteorological data from CONAGUA, using the Modified Fournier Index. Sea rise was recreated with sea rise projections and the piezometric level and distance to the coastline were considered. Finally, for land use, the secondary zoning of the Urban Development Programme and the land use coefficient were considered. Each factor was assigned a vulnerability differentiation, which defines the susceptibility of the territory to pollution. The results for relief show a greater vulnerability in residential and mixed tourist land use, with a frequency of 30 to 37 depressions, predominantly sinkholes and sinkholes -uvalas. For climate, the vulnerable zone was identified to the southeast of the city; for sea rise, it was found in the first kilometre with respect to the coastline, affecting 20% of the depressions. The most vulnerable land uses were commercial use, residential tourism, high-density residential and mixed use.